UNDERSTANDING THE CONVENTION ON SPECIES OF WILD FAUNA AND FLORA (CITES): A STUDY ON THE ILLEGAL WILDLIFE TRADE IN SUMATRA HELMETED HORNBILL - Sri Elmanita S; Sophia Listriani (Student Journal of International Law, 2023)
This study analyzes the implementation of Convention on Species of Wild Fauna and Flora (CITES) in dealing with the Illegal Wildlife Trade (IWT) of the helmeted hornbill (Rhinoplax vigil) in Sumatra and the government's role in saving the species from extinction. This study was conducted based on a normative juridical method.  The result showed that Law No. 5 of 1990 and Government Regulation No. 7 of 1999 on safeguarding all hornbills, including the helmeted hornbill is a sound reference on this issue. The high levels of protected animal trade in the Sumatran bird market through social media, animal hunting in conservation zones is proven. The government also helps to conserve helmeted hornbill by participating in CITES COP 17 in Johannesburg South Africa, building national and international collaboration, and in-situ and ex-situ conservation. The government has faced other challenges, such as unclear legal regulations, a lack of human resources, and environmental damage.